Análise do polimorfismo do gene TP53 (códon 72) e sua relação com a infecção pelo papilomavírus humano (HPV) em tumores de pênis - ROCHA, Thalita Moura Silva (2022)
Penile cancer (CaPe) has a low incidence in developed countries, but it represents 1/10 of all tumors that affect men in developing countries. Brazil has one of the highest incidences ever recorded, with the highest number of cases in the North and Northeast regions. The state of Maranhão accounts for 10.6% of all cases of CaPe diagnosed in the country, and has recently been considered the location with the highest incidence of the disease in Brazil and globally. CaPe has a multifactorial etiology, being associated with socioeconomic/behavioral factors and human papillomavirus (HPV) infection. The disease has become a serious public health problem in certain regions, mainly due to limitations in the therapeutic arsenal available for treatment, reflecting the scarcity of studies aimed at understanding the pathophysiological aspects and the genetic basis of these tumors. Therefore, the present study aimed to investigate the codon 72 polymorphism of the TP53 gene in CaPe and its association with HPV infection and p53 protein expression. For this, a prospective study was designed and included the recruitment of 53 patients with CaPe in three oncology referral hospitals in Maranhão (HCAB, HUUFMA, and HGTLF), between 2020 and 2022. All patients signed an informed consent form (TCLE) and were interviewed to collect socio-behavioral data. For allelic determination of codon 72 of the TP53 gene, peripheral blood samples were collected from each patient for DNA extraction from healthy cells. The DNA samples were submitted to qualitative PCR (Polymerase Chain Reaction) amplification using specific primer pairs for the Arginine amino acid determinant allele (ArgF/R) and the Proline allele (ProF/R). For HPV detection, small fragments of tumor were collected from each patient at the time of surgery. Tumor samples were stored in RNAlater solution and submitted to tumor DNA extraction. These samples were submitted to PCR (nested) for HPV detection using the generic primers PGMY09/11 (450 bp) in the first round, and the GP5+/GP6+ primers (170 bp) in the second. PCR products for HPV detection as well as allelic determination of codon 72 of TP53 were evaluated in 1.5% agarose gel. HPV-positive cases were sequenced by capillary electrophoresis to determine the viral genotype. Analysis of p53 protein expression was performed by immunohistochemistry, using an anti-p53 monoclonal antibody (DO-7) and following the protocol recommended by the manufacturer (Dako, Agilent Technologies). All tumors were reviewed by two pathologists to characterize the histopathological aspects. The results revealed a high frequency of homozygous arginine allele (Arg/Arg), detected in 88.6% of cases, and all other cases (26.4%) were heterozygous (Pro/Arg). About 66.7% of the cases were positive for HPV, with the high- risk type 16 being the most prevalent (67.9%). The analysis of p53 protein expression revealed positivity in 59.6% of the cases. When the data were associated with each other and with the clinical and histopathological aspects, there was an association between HPV positivity and the presence of koilocytosis (p=0.001). The absence of perineural invasion (p=0.002) and pT2 staging (p=0.016) were associated with cases without HPV-16 infection. Furthermore, an association was observed between HPV positivity and cases with the Arg/Arg genotype (p=0.004). The absence of p53 protein expression was associated with tumors without sarcomatoid transformation (p=0.012), in stage II (p=0.019), and the absence of koilocytosis (p=0.027). These findings support the role of HPV infection in CaPe and describe important aspects related to TP53 codon 72 polymorphism and virus infection, as has been reported in other HPV-associated cancers.